Experimental measurement and prediction of thermophysical properties of methyl tert-butyl ether (MTBE) with methanol, diisopropyl ether (DIPE) and N-methylaniline binary mixtures - Ali, Mohammed Rashid (2019)
Thermophysical properties of hydrocarbon mixtures play a vital role in process industries such as distillation, extraction operations, material and energy balance as well as solving problems in heat transfer, mass transfer, and fluid flow. Studies on thermophysical properties such as density and viscosity of liquid mixtures within a wide range of composition and temperatures are valuable sources of information for examining the relationship between the internal structure of the system and its physical properties. In this work density and viscosity of methyl tert-butyl ether (MTBE) with methanol, diisopropyl ether (DIPE) and N-methylaniline (NMA) binary liquid mixtures have been measured by using DMA 4500 M density meter and Anton Paar´s Stabinger Viscometer™ SVM™ 3000 at temperatures of 35 °C, 40 °C and 45 °C. The densities and viscosities of MTBE-methanol and MTBE-NMA binary mixtures show decreasing trends with the increase of MTBE composition at all temperature. On the contrary, binary mixture of MTBE-DIPE shows an increment in density and viscosity under the same condition. In addition, Jouyban-Acree equation has been used to predict density and viscosity where low mean absolute error (MAE) of 0.3 % and 2.2 % have been obtained. The excess molar volumes and viscosity deviation have been calculated using the density and viscosity experimental data and correlated with Redlich-Kister equation where a good fitted has been obtained. Sigmoid shapes of excess molar volumes have been obtained for all binary mixture. It has been found that in order to obtain a strong combination fuel, negative excess molar volumes are preferable. Thus binary mixtures of MTBE-methanol and MTBE-NMA must be mixed at high mole fraction of MTBE. However low mole fraction of MTBE must be used in the case of MTBE-DIPE binary mixture. The viscosity deviations of all binary mixtures are negative and were observed to decrease with an increase of temperatures. This indicates the strength of chemical or specific interaction for binary mixtures such as hydrogen binding between dissimilar molecules. Further investigation of molecular interaction has been performed using Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) and Proton Nuclear Magnetic Resonance (1H-NMR) spectroscopy analysis using ratios 3:7 and 7:3 of binary mixture. It has been observed that intermolecular interaction is more evident for ratio 7:3 for MTBE-methanol and MTBE-NMA. However, the variation in percentage composition of MTBE with DIPE of the individual components does not seem to affect significantly the spectrum of the binary mixture. Hence, this suggests that the intermolecular interaction between MTBE and DIPE is less dependent on the amount of DIPE present in the binary mixture.